Phylogenetic relationships, stage-specific expression and localisation of a unique family of inactive cysteine proteases in Sarcoptes scabiei - Fernando, Deepani D. (Parasit Vectors, 2018)
BACKGROUND: Scabies is worldwide one of the most common, yet neglected, parasitic skin infections, affecting a wide range of mammals including humans. Limited treatment options and evidence of emerging mite resistance against the currently used drugs drive our research to explore new therapeutic candidates. Previously, we discovered a multicopy family of genes encoding cysteine proteases with their catalytic sites inactivated by mutation (SMIPP-Cs). This protein family is unique in parasitic scabies mites and is absent in related non-burrowing mites. We postulated that the SMIPP-Cs have evolved as an adaptation to the parasitic lifestyle of the scabies mite. To formulate testable hypotheses for their functions and to propose possible strategies for translational research we investigated whether the SMIPP-Cs are common to all scabies mite varieties and where within the mite body as well as when throughout the parasitic life-cycle they are expressed. RESULTS: SMIPP-C sequences from human, pig and dog mites were analysed bioinformatically and the phylogenetic relationships between the SMIPP-C multi-copy gene families of human, pig and dog mites were established. Results suggest that amplification of the SMIPP-C genes occurred in a common ancestor and individual genes evolved independently in the different mite varieties. Recombinant human mite SMIPP-C proteins were produced and used for murine polyclonal antibody production. Immunohistology on skin sections from human patients localised the SMIPP-Cs in the mite gut and in mite faeces within in the epidermal skin burrows. SMIPP-C transcription into mRNA in different life stages was assessed in human and pig mites by reverse transcription followed by droplet digital PCR (ddPCR). High transcription levels of SMIPP-C genes were detected in the adult female life stage in comparison to all other life stages. CONCLUSIONS: The fact that the SMIPP-Cs are unique to three Sarcoptes varieties, present in all burrowing life stages and highly expressed in the digestive system of the infective adult female life stage may highlight an essential role in parasitism. As they are excreted from the gut in scybala they presumably are able to interact or interfere with host proteins present in the epidermis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-018-2862-0) contains supplementary material, which is available to authorized users.